2018
DOI: 10.1111/his.13689
|View full text |Cite
|
Sign up to set email alerts
|

PAX7 immunohistochemical evaluation of Ewing sarcoma and other small round cell tumours

Abstract: Although we confirmed that PAX7 is a sensitive marker for Ewing sarcoma, anti-PAX7 antibody also stained several Ewing sarcoma mimics, whose spectrum was distinct from NKX2-2-positive non-Ewing entities. Further studies are required to determine how PAX7 could be integrated into practice to classify small round cell tumours efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 14 publications
0
57
0
2
Order By: Relevance
“…Hence, many groups have evaluated several potential diagnostic markers such as FLI1, NKX2-2, and PAX7 that could be used instead of the highly unspecific marker CD99 [40,57,58]. However, to the best of our knowledge, none of these proposed IHC markers completely fulfills the requirements of providing very high sensitivity and specificity for EwS at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, many groups have evaluated several potential diagnostic markers such as FLI1, NKX2-2, and PAX7 that could be used instead of the highly unspecific marker CD99 [40,57,58]. However, to the best of our knowledge, none of these proposed IHC markers completely fulfills the requirements of providing very high sensitivity and specificity for EwS at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, none of these proposed IHC markers completely fulfills the requirements of providing very high sensitivity and specificity for EwS at the same time. While FLI1 is unable to confirm EwS cases with FET-non-FLI1 translocations [33,59], NKX2-2 and PAX7 lack specificity [60] and can be even strongly expressed in close morphological mimics such as EWSR1-NFATc2-positive sarcomas [40,57,58]. Besides, also Caveolin-1 [54,61], Cyclin-D1 [62], and NR0B1 [63] have been proposed as potential (auxiliary) IHC markers for EwS.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the published literature in the PubMed databank revealed 8 papers with at least minimal clinical information on 15 patients with tumors carrying the EWSR1-NFATC2 fusion [12, 13, 22, 2630] (Table 1). Fourteen more cases lacking clinical information are mentioned in three further studies with a special focus on the molecular profiling of ES and ESLT [20, 23, 24]. Of the cases with clinical information, there was a striking male predominance with 14 males and 4 females.…”
Section: Review Of the Published Literaturementioning
confidence: 99%
“…Rare mesenchymal tumors carrying EWSR1-NFATC2 fusions have been assigned to ESLTs, probably due to partial CD99 expression and/or involvement of the EWSR1 [2023]. However, recent studies demonstrate that not only histological features, but also the molecular profiles of such tumors differ from ESs [2426].…”
Section: Introductionmentioning
confidence: 99%
“…Another gene is GCKR, which play a significant role in cancer cell metabolism. The PAX7 gene play critical roles during fetal development and cancer growth [38]. Finally, IL2RA is an Interleukin 2 receptor subunit alpha protein involved in suppressing the activity of the immune system against tumor cells [39].…”
Section: Discussionmentioning
confidence: 99%